SMART PARKING GATE MENGGUNAKAN RFID BERBASIS ARDUINO DI UNIVERSITAS BANTEN JAYA - Yul Hendra; Waliadi Gunawan (Jurnal Ilmiah Sains dan Teknologi, 2020)
Radio Frequency Identification (RFID) has been now, widely used as security system room device, checking goods, noralthough as media for daily attendance in office areas. With this RFID system, it is expected that someone can carry out various activities more quickly, effectively and safely. The design of the Parking Gate Prototype aims to design a microcontroller tool,that is Parking Gate can be inform the motorist. In this design has several common parts that are used, namely ultrasonic sensors, Arduino, PC / laptop. While, for the entrance and exit areas of the parking area using a servo device, and Arduino UNO as the operation of the parking gate. Banten Jaya University is a campus located in Serang City, Banten Province and a provider of educational services of Informatics, Teacher Training and Engineering. The control and security of the parking area at Banten Jaya University is currently not optimal, because there is no information about the parking area and the maximum checking when leaving the parking area. So that, there is a risk of loss of vehicles and disorganized of it in parking vehicles. This study aims to create a parking gate system that utilizes RFID through a Kartu Tanda Penduduk (KTP) as a media to access the parking area. In this research, a parking gate system using RFID as the main media is produced to identify users who will enter or exit the parking area. The system development uses the Rapid Application Development (RAD) method by analyzing existing weaknesses in the current system, which was obtained from interviews with the infrastructure facilities of Banten Jaya University.